A typology for land restoration through agroforestry - CGIAR Research Program on Forests, Trees and Agroforestry (2020)
The typology has been finalized and published in the Journal Land. van Noordwijk M, Gitz V, Minang PA, Dewi S, Leimona B, Duguma L, Pingault N, and Meybeck A. 2020. People-Centric Nature-Based Land Restoration through Agroforestry: A Typology. Land 2020, 9(8), 251; https://doi.org/10.3390/land9080251